ANALISIS PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN MODIFIKASI, SPRINGATE, DAN GROVER PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - MULYADI MULYADI; RUDY RUDY; HIDAYAT DARWIS (JURNAL TEKNIK INDUSTRI, 2018)
The purpose of this study is to find out how the condition of the company after using the prediction model Altman Modified, Springate, Grover and to see which prediction model has the highest level of accuracy in predicting the potential occurrence of financial distress on property and real estate companies. The method used is quantitative descriptive method. The results obtained from this study are Model Altman Modified predicts 9 samples potentially experiencing financial distress, 12 samples are in the gray zone, and 49 samples are predicted not potentially experiencing financial distress. In Springate Model predicts 43 samples potentially experiencing financial distress and 27 other samples did not have the potential to experience financial distress. While the Grover Model predicts 62 samples are not potentially experiencing financial distress and 8 others are predicted to potentially experience financial distress. Of the three prediction models, the Springate Model received the lowest error rate in predicting financial distress with a percentage error of 31% so that this prediction model was selected as a recommendation in predicting financial distress in property and real estate firms.Keywords: Financial Distress, Altman Modified, Springate, Grover